Epidemiological and Socio-demographic Characters of Glucocorticoids Misuse among Premenopausal Women in Thi-Qar, Southern Iraq - Asia Hameed Saddam; Majid Abdulwahab Maatook; Mahmood Thamer Altemimi (University of Thi-Qar Journal of Science, 2023)
Glucocorticoids (GCs) are widely accessible over-the-counter (OTC), liberally recommended by locals medical practitioner, and frequently misused by women for the purpose of treatment of skin conditions, joint pains, febrile illnesses and asthma. Unfortunately, ladies misuse a lot of over-the-counter GCs and glucocorticoids containing cosmetic creams, both imported and locally blended in order to deposit fat as a connection between beauty and propensity. The objectives of the study were to evaluate the epidemiological and socio-demographic characteristics of GCs misuse among reproductive women in the South of Iraq. Methods: a cross-sectional study was conducted on 251 reproductive-aged women who were misusing GCs for any cause and attending Thi-Qar Specialized Diabetes, Endocrine and Metabolism Center (TDEMC) in Nasiriya City. They were evaluated for demographic characteristics, medical and social histories, and then examined carefully for any signs of GCs misuse. Results: The mean ages of women were 33.21±8.6 years, BMI 30.68±7.3 Kg/m², and 208 (82.9%) women were eitheroverweight or obese. More than half (51.3%) of the women were misusing two or more forma of GCs and one quarter(26.7%) of them were misusing tablets. The types of GCs misused were presented as 77.7% dexamethasone, 19.5%prednisolone, 22.3% hydrocortisone, 21.1% betamethasone, 17.5% local GCs types, and 13.5% Inhaler GCs types. Themajor source of GCs misuse was pharmacy 201 (80.1%) and 18 (7.2%) from street vendors. Approximately, all women hadmany features of GCs-induced adverse effects and there were many misconceptions about their safety like 41.8% .